2006
DOI: 10.2172/911682
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alternate Materials for Coated Particle Fuels for the Gas-Cooled Fast Reactor. Laboratory Directed Research and Development Program FY 2006 Final Report

Abstract: Candidate ceramic materials were studied to determine their suitability as Gas-Cooled Fast Reactor particle fuel coatings. The following ceramics examined in this work: TiC, TiN, ZrC, ZrN, AlN, and SiC. The studies focused on (i) chemical reactivity of the ceramics with fission products palladium and rhodium, (ii) the thermomechanical stresses that develop in the fuel coatings from a variety of causes during burnup, and (iii) the radiation resiliency of the materials. The chemical reactivity of TiC, TiN, ZrC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Zirconium carbide and zirconium nitride both offer benefits as inert matrix fuel materials for next generation nuclear power plants. However, the scatter of thermophysical data for ZrN in the literature has led to reviews comparing inert matrix fuel candidates reporting the thermal conductivity of ZrN as much lower than the ZrC x N y phases presented in this work, sometimes with values of around 10 Wm À1 K À1 [40,41]. It has also been shown that carbon contamination from the carbothermic reduction and nitridation route is present even after long sintering times and high temperatures, however all mixed phases had excellent thermal conductivity values.…”
Section: Discussionmentioning
confidence: 86%
“…Zirconium carbide and zirconium nitride both offer benefits as inert matrix fuel materials for next generation nuclear power plants. However, the scatter of thermophysical data for ZrN in the literature has led to reviews comparing inert matrix fuel candidates reporting the thermal conductivity of ZrN as much lower than the ZrC x N y phases presented in this work, sometimes with values of around 10 Wm À1 K À1 [40,41]. It has also been shown that carbon contamination from the carbothermic reduction and nitridation route is present even after long sintering times and high temperatures, however all mixed phases had excellent thermal conductivity values.…”
Section: Discussionmentioning
confidence: 86%